Sharia Governance and Risk Mitigation in E-Wallets: Implications for SDG 8 - Abdul Razak, Nurul Asikin Binti; Ahmad, Shofian Bin; Zakaria, Zamzuri Bin; Wira, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid advancement of financial technology (fintech) has driven the adoption of e-wallets as a widely used medium for digital transactions. However, within the Islamic finance context, challenges such as Sharia compliance, transaction security, and effective governance persist. This study investigates the role of Sharia governance in mitigating legal, operational, and reputational risks associated with e-wallets and explores its implications for Sustainable Development Goals (SDG) 8, which emphasizes decent work and economic growth. Using a qualitative approach and secondary data analysis, the study examines Sharia governance frameworks, compliance challenges, and oversight mechanisms, including the role of the Sharia Advisory Board, periodic audits, and transparency in fund management. Findings reveal that robust Sharia governance reduces compliance uncertainties, enhances consumer trust, and stabilizes the industry. Furthermore, systematic governance in e-wallets directly supports SDG 8 by fostering financial inclusion, creating decent job opportunities, and driving sustainable economic growth. The study emphasizes the need for standardized Sharia compliance protocols, regular audits, and collaboration between regulatory bodies and e-wallet providers to ensure effective and consistent adherence to Islamic principles. The insights are crucial for stakeholders to develop a resilient Islamic fintech ecosystem that aligns technological innovation with Sharia values and global sustainability goals